Sex Differences in Circulating Biomarkers of Cardiovascular Disease - Lau, Emily S. (J Am Coll Cardiol, 2019)
BACKGROUND: Differences in proteomic profiles between men and women may provide insights into the biologic pathways that contribute to known sex differences in cardiovascular disease (CVD). OBJECTIVES: To investigate sex differences in circulating biomarkers representative of biologic pathways implicated in the development of CVD among Framingham Heart Study participants. METHODS: We measured 71 circulating CVD protein biomarkers in 7184 participants (54% women, mean age 49). Multivariable models were used to evaluate the associations of sex, menopause and hormone status with biomarkers. Cox models were used to examine whether sex modified the association of biomarkers with incident CVD. RESULTS: Of 71 biomarkers examined, 61 (86%) differed significantly between men and women, of which 37 were higher in women (including adipokines and inflammatory markers such as leptin and CRP) and 24 were higher in men (including fibrosis and platelet markers such as MMP8 and TIMP1, FDR q<0.05 for all). Sex differences in biomarker profiles were most pronounced between pre-menopausal women vs men, with attenuated sex differences among post-menopausal women not taking hormone replacement therapy. Sex modified the association of specific biomarkers with incident CVD, including CD14 and ApoB (P(interaction) <0.05 for all). CONCLUSIONS: In a predominantly Caucasian population, we identified widespread sex differences in circulating biomarkers that reflect distinct pathways implicated in CVD including inflammation, adiposity, fibrosis, and platelet homeostasis. Menopause and hormone status accounted for some but not all the observed sex differences. Further investigation into factors underlying sex-based differences may provide mechanistic insight into CVD development.